2000
DOI: 10.1080/00071660086330
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition: The integrative science

Abstract: 1. Nutrition is a vitally important part of the production environment but also interacts with many other disciplines. 2. Modern breeding methods involving selection for a wider range of characteristics are likely to result in new genotypes with different nutritional needs. Geneticists and nutritionists will have to work closely together in the future to identify nutritional needs of these birds. 3. Collaboration between nutrition and other disciplines has been important in maintaining efficient poultry produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In the present study, it was observed that the inclusion of phytase in AACM diets resulted in a reduction of pancreas weight, which may be attributed to the interaction between phytic acid and digestive enzymes. Phytate was found to bind to endogenous proteases such as trypsin and chymotrypsin, as well as their precursors, during their passage through the digestive tract [50]. At certain concentrations of phytate, a ternary protein-metal-phytate complex can be formed, as both enzymes and their precursors have an affinity for Ca, further reducing the bioavailability of proteins and minerals [51].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was observed that the inclusion of phytase in AACM diets resulted in a reduction of pancreas weight, which may be attributed to the interaction between phytic acid and digestive enzymes. Phytate was found to bind to endogenous proteases such as trypsin and chymotrypsin, as well as their precursors, during their passage through the digestive tract [50]. At certain concentrations of phytate, a ternary protein-metal-phytate complex can be formed, as both enzymes and their precursors have an affinity for Ca, further reducing the bioavailability of proteins and minerals [51].…”
Section: Discussionmentioning
confidence: 99%
“…History of poultry nutrition: K. Elwinger et al established the full aetiology of the disorder (Whitehead, 2000). The subsequent use of biotin as a routine feed supplement for broilers led to larger-scale industrial synthesis and marked reduction in cost.…”
Section: Disease Syndromes Related To Vitaminsmentioning
confidence: 99%
“…FURTHER FUNCTIONS RELATED TO VITAMINS Initially vitamin supply was mainly aimed at safeguarding optimal performance including lowest morbidity and mortality. Further criteria, where dosages above the normal nutritive requirements were used, for example for an improvement in immunological status (Leeson and Summers, 2001;Whitehead, 2000;Butcher and Miles, 2011). Investigations on these subjects started decades ago and are still ongoing at present.…”
Section: Disease Syndromes Related To Vitaminsmentioning
confidence: 99%
“…Robinson et al (1991) observed 700 g difference in BW between ad libitum and the feed restricted groups at sexual maturity, out of which 62% was fat. Feed restricted birds are not free from hunger, but they have the welfare benefit of reduced metabolic disorders and mortality (Whitehead, 2000). However, feed restriction-induced stress in birds, particularly during early phase of growth, when metabolic requirements are high (Mench, 2002).…”
Section: Introductionmentioning
confidence: 99%